1978
DOI: 10.1002/chin.197820023
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SURFACE TENSION OF LIQUID SELENIUM, TELLURIUM, AND MELTS OF THE THALLIUM‐TELLURIUM SYSTEM

Abstract: Die Kurven für die Temp.‐Abhängigkeit der Oberflächenspannung weisen Besonderheiten auf, die die Strukturumwandlungen in flüssigem Se und Te widerspiegeln.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Lang [4] reviewed the studies on the surface tension of molten bismuth based on 13 previous papers in 1973, and Keene [8] reviewed the individual values given in the 16 references for surface tension of molten bismuth in 1993. The results, methods, conditions and the temperature range for the surface tension measurement of molten bismuth are presented in Table 1[1–19] and the surface tension of molten bismuth measured by various investigators are shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lang [4] reviewed the studies on the surface tension of molten bismuth based on 13 previous papers in 1973, and Keene [8] reviewed the individual values given in the 16 references for surface tension of molten bismuth in 1993. The results, methods, conditions and the temperature range for the surface tension measurement of molten bismuth are presented in Table 1[1–19] and the surface tension of molten bismuth measured by various investigators are shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…The reported surface tension and the temperature dependence of molten bismuth have been measured with unknown oxygen partial pressure, and there exists a large difference among the values [1–19]. One of the main reasons for the differences is that the measurement methods and the measurement conditions of surface tension are different, especially the oxygen potentials (the oxygen partial pressure in atmosphere) of measuring system.…”
mentioning
confidence: 99%
“…The temperature dependence of the surface tension ␥ is included from Ref. 21, although it does not vary by more than 2% over this temperature range.…”
mentioning
confidence: 99%
“…Since ⌬␤ is determined by the local radius of curvature (rϳ150 mm͒, the beam height at the sample position (hϳ0.1 mm͒, and incident angle ␣, this leads to k min ϭ2h/(r)ϭ0.0064 Å Ϫ1 , independent of q z . From the Ga surface tension 49 and the experimental resolution, we calculate the capillary wave contribution with 0 ϭ0.37Ϯ0.027 Å, and the other parameters, d and , are unchanged. The reflectivity data are well described over the entire measured temperature range ͑i.e., up to 170°C͒.…”
Section: ͑2͒mentioning
confidence: 99%